2016
DOI: 10.1016/j.ijgo.2015.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation in women with endometriosis and chronic pelvic pain

Abstract: Women with endometriosis develop progressive social isolation after the onset of chronic pelvic pain. This finding is important for the multidisciplinary management of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 28 publications
1
40
0
4
Order By: Relevance
“… 7 , 8 This suggests a detrimental effect of CPP on personal relationships and social support. A previous study showed progressive social isolation in women with endometriosis who developed pelvic pain, 27 hampering their relationships with partners, family, and friends. In agreement with previous findings, CPP also hampered activities of daily living, as shown by the results for the physical health domain.…”
Section: Discussionmentioning
confidence: 95%
“… 7 , 8 This suggests a detrimental effect of CPP on personal relationships and social support. A previous study showed progressive social isolation in women with endometriosis who developed pelvic pain, 27 hampering their relationships with partners, family, and friends. In agreement with previous findings, CPP also hampered activities of daily living, as shown by the results for the physical health domain.…”
Section: Discussionmentioning
confidence: 95%
“…Such findings imply that when women have stable social support, they may be less vulnerable to the negative emotional and physical manifestations of PD. For example, social isolation is a noted phenomenon in other chronic medical conditions, including painful disorders such as endometriosis, and may lessen physical and activity conditioning(Mellado et al, 2016).The interconnectivity of psychological impacts, social withdrawal, and physical inactivity may be central to pain propagation and interference in PD.Another example of the importance of social factors is the role of maternal responses, including maternal anxiety, in women's understandings of their own menstrual pain. Recent quantitative research has explored the ways parental psychological processes and behaviours may have an impact on pain functioning in children(Timmers, Simons, Hernandez, McCracken, & Wallace, 2019).…”
mentioning
confidence: 99%
“…Like other chronic pain conditions, CPP is influenced by and associated with many psychological and social factors, such as depression, anxiety, post‐traumatic stress disorder, substance abuse, catastrophization, hypervigilance, and helplessness 4,5 . With all these factors evolving around the CPP experience, it is no surprise that patients may have feelings and attitudes leading to social isolation, including: avoiding intimacy; self‐isolating from partners; friends, and family; perceptions that others lack understanding about the disease, and a sense of resignation 6 . It has been well described that patients with specific CPP conditions face obstacles in receiving proper care, as seen in patients with endometriosis who experience a delay of 3.8 years on average between symptom onset and seeking medical care, and a delay in diagnosis ranging from 5–8 years 7,8 .…”
Section: Chronic Pain Patients Were Underserved Before the Pandemicmentioning
confidence: 99%